HUBUNGAN KOMUNIKASI TERAPEUTIK PERAWAT DENGAN TINGKAT KEPUASAN PASIEN RAWAT JALAN DI POLI PENYAKIT DALAM RUMAH SAKIT KARTIKA CIBADAK SUKABUMI - ginanjar, deden (Jurnal Kesehatan & Disiplin Ilmu, 2025)
Nurses' therapeutic communication has an important role in supporting the level of patient satisfaction. Having therapeutic communication skills for nurses makes it easier to establish trusting relationships with patients, so that they are more effective in achieving the nursing care goals that have been implemented and will provide professional satisfaction in nursing services. The aim of this research was to determine the relationship between therapeutic communication and the level of satisfaction of outpatients at the internal medicine clinic at Kartika Cibadak Hospital. The research design used was cross-sectional. The number of samples in this study was 96 patients. Sampling used purposive sampling. The instrument used was a questionnaire with a Likert scale. Univariate and bivariate data analysis. The results of the research were that 28 patients (57.1%) had good nurse therapeutic communication, the patients said they were satisfied, 5 patients (45.5%) had poor nurse therapeutic communication, the patients said they were dissatisfied. Statistical tests using the Chi-Square Test carried out with Two-Sample Kolmogorov-Smirnov analysis obtained a p value = 1.000. The conclusion of this research is that there is no relationship between nurses' therapeutic communication and the level of satisfaction of outpatients in the internal medicine clinic at Kartika Cibadak Hospital, Sukabumi with a p value of 1,000.